I, sniper : a Bob Lee Swagger novel - Hunter, Stephen, 1946- (Hunter, Stephen, 1946- Bob Lee Swagger novel., 2009)
Special Agent Nick Memphis enlists the help of retired Marine sniper Bob Lee Swagger to unravel a sophisticated conspiracy involving the deaths of four famed '60s radicals--a conspiracy that would require the highest level of warcraft by the most superb special operations professionals.